CBX7 and miR‐9 are part of an autoregulatory loop controlling p16INK4a. Issue 6 (29th September 2015) - O'Loghlen, Ana; Brookes, Sharon; Martin, Nadine; Rapisarda, Valentina; Peters, Gordon; Gil, Jesús
Summary: Polycomb repressive complexes (PRC1 and PRC2) are epigenetic regulators that act in coordination to influence multiple cellular processes including pluripotency, differentiation, cancer and senescence. The role of PRCs in senescence can be mostly explained by their ability to repress the INK4/ARF locus. CBX7 is one of five mammalian orthologues of Drosophila Polycomb that forms part of PRC1. Despite the relevance of CBX7 for regulating senescence and pluripotency, we have a limited understanding of how the expression of CBX7 is regulated. Here we report that the miR‐9 family of microRNAs (miRNAS) downregulates the expression of CBX7. In turn, CBX7 represses miR‐9‐1 and miR‐9‐2 as part of a regulatory negative feedback loop. The miR‐9/CBX7 feedback loop is a regulatory module contributing to induction of the cyclin‐dependent kinase inhibitor (CDKI) p16 INK 4a during senescence. The ability of the miR‐9 family to regulate senescence could have implications for understanding the role of miR‐9 in cancer and aging.